Effects of Different Ratios of Mixed Silage of Licorice Stems and Leaves and Whole Corn on Fermentation Quality, Microbial Diversity, and Aerobic Stability - Qifeng Gao; Yuliang Sun; Limin Tang; Haonan Liu; Chenchen Yang; Yulan Ren; Fangpeng Liu; Chunying Jia; Houjun Yu; Tao Jiang (Fermentation)
This experiment aimed to investigate the effects of varying proportions of mixed silage on fermentation quality, microbial diversity, and aerobic stability. The mixed silage samples (G10Y0, G9Y1, G8Y2, G7Y3, G6Y4, G5Y5, G4Y6, G3Y7, G2Y8, G1Y9, and G0Y10) were prepared with a 10% mass ratio of licorice stems and leaves (G) to whole-plant corn (Y) mixed silage. After sealing for 60 days, the cans were opened, and their nutrient content and fermentation quality were assessed. Based on the nutrient content, fermentation quality parameters, and the optimal utilization of licorice stems and leaves, three groups were selected for microbial flora measurement and aerobic stability assessment. The test results indicated that as the proportion of whole-plant corn increased, the crude protein (CP) content in each mixed silage proportion significantly decreased (p < 0.05). Additionally, the pH values across the various proportions exhibited an overall downward trend. Starting from the G5Y5 group, the pH values for each group were consistent, remaining below 4.2. At the phylum level, the dominant bacterial phylum in each group was Firmicutes, followed by Proteobacteria, while the abundance of Bacteroidetes in the G5Y5 group was significantly higher than that in the other groups (p < 0.05). At the genus level, Lentilactobacillus, Citrobacter, and Weissella were identified as the dominant genera. The abundance of Lentilactobacillus in the G4Y6 group was significantly greater than that in the other groups (p < 0.05). Additionally, the abundance of the Citrobacter genus in the G6Y4 group was significantly higher than in the other groups (p < 0.05). Furthermore, the Shannon index of alpha diversity in the G5Y5 group was significantly higher than in the other two groups (p < 0.05). With the extension of aerobic exposure days, the pH value and the number of yeasts and molds in each group gradually increased, while the number of lactic acid bacteria gradually decreased. On the 15th day of aerobic exposure, the pH value of the G5Y5 group was significantly lower than that of the other groups (p < 0.05), and the number of lactic acid bacteria was significantly higher than that of the G6Y4 group (p < 0.05). In summary, the mixed silage from the G5Y5 group exhibits the highest nutritional value, attributed to its superior fermentation quality. Additionally, the microbial diversity and uniformity in the G5Y5 group are enhanced, resulting in a more stable fermentation environment and optimal aerobic stability.